Pengembangan Modul Edukasi Hukum Waris Islam Berbasis Digital Untuk Meningkatkan Literasi Masyarakat Muslim - Hamdi, Fahmi; Hasanah, Tuti (Interdisciplinary Explorations in Research Journal, 2023)
Abstract The low level of literacy among Muslims regarding Islamic inheritance law (faraid) remains an issue that has the potential to cause family conflicts and injustice in the distribution of inherited assets. This community service activity aims to develop a digital-based Islamic inheritance law education module to improve literacy and understanding among the community. The method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The module is designed to be interactive and easy to use, equipped with learning videos, quizzes, and an inheritance distribution calculator. The results of the trial show an increase in the community's understanding of the concept of faraid and how to apply it. This digital module also helps expand access to Islamic inheritance law education and has the potential to reduce family conflicts related to inheritance. Thus, digital-based educational modules are an effective solution for improving Islamic inheritance law literacy in the community. Keywords: Islamic inheritance law, faraid, digital module, community literacy. Abstrak Rendahnya literasi masyarakat Muslim terhadap hukum waris Islam (faraid) masih menjadi permasalahan yang berpotensi menimbulkan konflik keluarga dan ketidakadilan dalam distribusi harta warisan. Kegiatan pengabdian kepada masyarakat ini bertujuan mengembangkan modul edukasi hukum waris Islam berbasis digital untuk meningkatkan literasi dan pemahaman masyarakat. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE yang meliputi analisis, desain, pengembangan, implementasi, dan evaluasi. Modul dirancang interaktif dan mudah digunakan, dilengkapi video pembelajaran, kuis, serta kalkulator pembagian warisan. Hasil uji coba menunjukkan adanya peningkatan pemahaman masyarakat tentang konsep faraid dan cara penerapannya. Modul digital ini juga membantu memperluas akses pembelajaran hukum waris Islam dan berpotensi mengurangi konflik keluarga terkait warisan. Dengan demikian, modul edukasi berbasis digital menjadi solusi efektif untuk meningkatkan literasi hukum waris Islam di masyarakat.